Pollution absorbtion of green open space: A comparative review between Singapore and Jakarta urban areas - Putri, Tri Riska; Koestoer, Raldi Hendro (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Rapid urbanization has significantly increased industrial activity, transportation, and energy use in cities, increasing air pollution. In addition to having a detrimental effect on the ecosystem, air pollution raises the risk of heart disease, respiratory conditions, and early mortality. Green open space is seen as a natural way to lower air pollution because of the vegetation's capacity to absorb pollutants like PM2.5 and PM10. Method: This SLR analysis combines quantitative bibliometry and descriptive research methods. Findings: The study results show that GOS plays an important role in reducing air pollutant concentrations, improving air quality, and providing health benefits to the community. However, the effectiveness of GOS is influenced by factors such as vegetation type, green area area, and urban spatial planning. Limited land, lack of integration in urban planning, and low public awareness are major problems in GOS development. In addition, this study found the potential to optimize GOS through innovations such as vertical green spaces and green roofs. Conclusion: This study also found that GOS should be included in sustainable urban spatial planning policies to improve air quality, reduce pollution impacts on health, and create a healthier and more comfortable urban environment for people by optimizing the GOS. To ensure the GOS development can go smoothly and sustainably in the future, it is required to have scientifically based policy recommendations. Novelty/Originality: This study assesses GOS's capacity to absorb air pollution by contrasting case studies from Indonesia and Singapore.